Pengaruh Keputusan Investasi, Keputusan Pendanaan Dan Kebijakan Dividen Terhadap Nilai Perusahaan Pada Pt Bukit Asam Tbk Periode 2015-2024 - Maria Serlina Tuti; Jamaludin Jamaludin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of Investment Decisions (Price Earnings Ratio), Financing Decisions (Debt to Equity Ratio), and Dividend Policy (Dividend Payout Ratio) on Firm Value (Price to Book Value) at PT Bukit Asam Tbk during the period 2015–2024. This research employs a quantitative associative approach using secondary data obtained from the company’s financial statements. The data analysis methods include descriptive statistics, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation tests), simple linear regression analysis, multiple linear regression analysis, hypothesis testing (partial t-test and simultaneous F-test), and the coefficient of determination (R²). The results indicate that Investment Decisions (PER) have a negative and significant effect on Firm Value (PBV), with a t-value of –3.110 and a significance level of 0.021 < 0.05. Financing Decisions (DER) have a negative but insignificant effect on Firm Value (PBV), with a t-value of –0.137 and a significance level of 0.895 > 0.05. Meanwhile, Dividend Policy (DPR) also has no significant partial effect on Firm Value (PBV), with a t-value of 1.411 and a significance level of 0.208 > 0.05. The results of the simple linear regression analysis show that each independent variable has a different relationship with PBV. Simultaneously, the F-test results indicate that PER, DER, and DPR jointly have a significant effect on Firm Value (PBV), with an F-value of 7.927 and a significance level of 0.016 < 0.05. The R-square value is 0.799, indicating that 79.9% of the variation in Firm Value (PBV) can be explained by PER, DER, and DPR, while the remaining 20.1% is influenced by other variables outside the research model.